DEVELOPING LEARNING MEDIA OF RECOUNT TEXTS FOR VOCATIONAL HIGH SCHOOL STUDENTS - Novita Sari; Soni Mirizon; Rita Inderawati (University of Kuningan, 2021)
This study was aimed to develop interactive multimedia of recount texts in teaching English in one Public Vocational High School in Palembang. In specific, this study was intended to see whether or not the developed interactive multimedia had validity, practicality, and potential effect. The subject of the study was the tenth-graders of Multimedia Study Program of the school. This development research applied Analysis, Design, Development, Implementation, and Evaluation (ADDIE) design. The formative evaluation was done through one to one evaluation, small group evaluation, and field test. The findings showed that the validity mean score of the developed product was 3.71, categorized as very high validity level. The practicality mean score in one-to-one evaluation was 3.69, in small group evaluation was 3.65, and in field test was 81.37, categorized as very high practicality level. The material of the reading test also had potential effect. It pointed out that there were 33 participants (94.28%) out of 35 participants in the test of reading achieved the minimum mastery criterion, which was 71.